Random amplification of polymorphic DNA reveals clonal relationships among enteropathogenic Escherichia coli isolated from non-human primates and humans - Carvalho, V. M.; Irino, K.; Onuma, D.; de Castro, A. F. Pestana (Associação Brasileira de Divulgação Científica (ABRADIC), 2007)
Enteropathogenic Escherichia coli ( EPEC) strains are important agents of infantile diarrhea all over the world, gaining even greater importance in developing countries. EPEC have also been isolated from various animal species, but most isolates belong to serotypes that differ from those recovered from humans. However, it has been demonstrated that several isolates from non- human primates belong to the serogroups and/ or serotypes related to those implicated in human disease. The objective of this study was to evaluate the genetic differences between thirteen strains isolated from non- human primates and the same number of strains isolated from human infections. Human isolates belonged to the same serogroup/ serotype as the monkey strains and the evaluation was done by analysis of random amplified polymorphic DNA. Dendrogram analysis showed that there was no clustering between human and monkey strains. Human and non- human isolates of the EPEC serotypes O127:H40 and O128:H2 shared 90 and 87% of their bands, respectively, indicating strong genomic similarity between the strains, leading to the speculation that they may have arisen from the same pathogenic clone. To our knowledge, this study is the first one comparing genomic similarity between human and non- human primate strains and the results provide further evidence that monkey EPEC strains correlate with human EPEC, as suggested in a previous investigation.
Keywords: Escherichia coli; enteropathogenic Escherichia coli; attaching and effacing Escherichia coli; attaching and effacing; monkey; random amplified polymorphic DNA